Mobile cloud computing for smartphones: Application development model and application piracy control / Atta Ur Rehman Khan - Khan, Atta Ur Rehman (2014)

(untitled)
In the past few years, smartphones have emerged as a new computing platform that supports a wide range of complex applications. Unfortunately, the ascend of smartphones to be the primary computing platform for mobile users is hampered by constrains such as limited processing power, memory, storage, and battery life. This problem is compounded by the fact that advanced features and complexity of applications demand an ever increasing computational power and energy. These constrains can be circumvented by taking advantage of mobile cloud computing technology, which has great potential to make mobile devices resourceful and energy-efficient by enabling them to offload resource intensive computational tasks to the resource-rich cloud. The challenge in doing so is that the traditional smartphone application models do not support computation offloading. Therefore, a specialized application model that is optimized for mobile environments is required. In order to propose a new application model that supports computation offloading in mobile environments, this work starts by identifying the unique characteristics of mobile cloud computing, followed by a qualitative comparison of well-known application models to ascertain their pros and cons. An online survey was conducted to investigate the smartphone usage patterns, user’s perception on resource intensive applications, their smartphone enhancement preferences, and behavior towards the adoption of mobile cloud computing in terms of cost and privacy. One of the findings of this survey is that mobile users are open to the use of cloud technology to extend the resources and capabilities of their smartphones, which reinforces the need for an application model that supports computation offloading. This study then proceeds to propose a new mobile cloud application model that supports multiple mobile cloud computing features, makes context-aware offloading decisions, and offers development support for a wide range of applications. The proposed model is tested using ten prototype applications in three experimental setups. An analysis of the experimental results shows that the proposed model meets all of its objectives. A qualitative comparison with other models proves that the proposed model supersedes many of the existing models. The only reliable method to calculate the offloading time and energy consumption of a mobile cloud application model is to implement its prototype applications in a real environment, which is time consuming and resource exhaustive. This method is also restrictive in terms of experimental setup if a researcher wishes to test the impact of various parameters and resources. Therefore, a mathematical model is proposed to calculate the offloading cost of application models and provide a base for the development of mobile cloud computing simulators. Offloading applications for execution in the cloud to enhance performance introduces the possibility of a new threat, i.e., application piracy. This problem is addressed by proposing a novel application licensing framework for mobile cloud environment. The proposed framework is formally verified, implemented, and tested in real environment with a conclusion that it is lightweight and incurs a negligible overhead on the smartphone.